2017
DOI: 10.1111/bph.13821
|View full text |Cite
|
Sign up to set email alerts
|

Selective and state‐dependent activation of TRESK (K2P18.1) background potassium channel by cloxyquin

Abstract: Cloxyquin activates TRESK by a Ca /calcineurin-independent mechanism. The drug is specific for TRESK within the K channel family and useful for studying TRESK currents in native cells. The state-dependent pharmacological profile of this channel should be considered in the development of therapeutics for migraine and other nociceptive disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 41 publications
3
46
0
Order By: Relevance
“…The A2797 compound activated mTRESK current about 4-fold at a 100 mM concentration. This degree of activation was similar to the previously reported effect of cloxyquin (Lengyel et al, 2017). However, as opposed to the relative selectivity of cloxyquin for TRESK in the K 2P family, A2797 also activated TREK-2, TASK-2, and TRAAK channels.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The A2797 compound activated mTRESK current about 4-fold at a 100 mM concentration. This degree of activation was similar to the previously reported effect of cloxyquin (Lengyel et al, 2017). However, as opposed to the relative selectivity of cloxyquin for TRESK in the K 2P family, A2797 also activated TREK-2, TASK-2, and TRAAK channels.…”
Section: Discussionsupporting
confidence: 90%
“…The stimulatory effect of cloxyquin was independent of the Ca 21 /calcineurin pathway, suggesting that cloxyquin is a direct activator of the channel. We have also shown that cloxyquin activates TRESK in isolated mouse DRG neurons (Lengyel et al, 2017). In the present study, we have produced 28 chemically modified analogs of cloxyquin and examined their effects on TRESK channels.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Furthermore, cloxyquin-mediated potassium channel activation has been reported. It selectively targets TRESK (K 2P channel family) and substantially activates the background potassium current, suggested for further development to be a promising therapeutic ingredient for migraine and other types of nociceptive pain [7,8]. Recently, the neuroprotective effect of cloxyquin derivative (nitroxoline) has been reported in H 2 O 2 -induced human neuronal cells [9].…”
mentioning
confidence: 99%